Ten year's work in an apple orchard - Derr, Homer (My University, 1900)
Introduction: The question of Apple growing interests nearly every farmer, as it is a crop that is easily grown, succeeding in most localities, and furnishing, at small expense in time, a large amount of nourishing and healthy food. Success in apple culture hinges upon the correct solution of many problems. In this thesis we shall briefly discuss several of these problems which arise in the first ten years of an orchard’s life, beginning from the selection of a location. In selecting a site for an orchard, convenience cannot be left out of the consideration. But exposure and kind of soil are of chief importance. In Kansas, and in the majority of places, a northern, or even better, a north-eastern slope is best; and, likewise, the second bottom or lower uplands, the choicest. It is often said that apples will do well on any high, strong, well drained soil, that will grow good wheat or corn, and this is generally found true. If the soil is not mellow and deep, - what we would call a permanent sub-soil, - then, we must use a sub-soiler. All orchard lands should be thoroughly surface drained and sub-drained. No orchard can endure for a great length of time with stagnant water either on the surface or within the soil. The selection of trees is an important part of orcharding, for upon care and judgement in this, depend largely the future profits of the investment. Strong, stocky, and vigorous one or two old trees, called “whips” by nurserymen, having well developed root systems, are preferable. Trees of this type and age are more satisfactory and profitable in time, and suffer less in transplanting, cost less, and are much more easily handled than older ones. Buy of the nearest responsible nurseryman.
Citation: Derr, Homer. Ten year's work in an apple orchard. Senior thesis, Kansas State Agricultural College, 1900.
Morse Department of Special Collections
Keywords: Apple; Kansas; Orchard; Cultivation; Theses